Capsular Polysaccharide of Mycoplasma ovipneumoniae Induces Sheep Airway Epithelial Cell Apoptosis via ROS-Dependent JNK/P38 MAPK Pathways. (7th March 2017) - Jiang, Zhongjia; Song, Fuyang; Li, Yanan; Xue, Di; Zhao, Ning; Zhang, Jiamei; Deng, Guangcun; Li, Min; Liu, Xiaoming; Wang, Yujiong
Abstract : In an attempt to better understand the pathogen-host interaction between invading Mycoplasma ovipneumoniae ( M. ovipneumoniae ) and sheep airway epithelial cells, biological effects and possible molecular mechanism of capsular polysaccharide of M. ovipneumoniae (CPS) in the induction of cell apoptosis were explored using sheep bronchial epithelial cells cultured in air-liquid interface (ALI). The CPS of M. ovipneumoniae was first isolated and purified. Results showed that CPS had a cytotoxic effect by disrupting the integrity of mitochondrial membrane, accompanied with an increase of reactive oxygen species and decrease of mitochondrial membrane potential (Δ Ψ m ). Of importance, the CPS exhibited an ability to induce caspase-dependent cell apoptosis via both intrinsic and extrinsic apoptotic pathways. Mechanistically, the CPS induced extrinsic cell apoptosis by upregulating FAS/FASL signaling proteins and cleaved-caspase-8 and promoted a ROS-dependent intrinsic cell apoptosis by activating a JNK and p38 signaling but not ERK1/2 signaling of mitogen-activated protein kinases (MAPK) pathways. These findings provide the first evidence that CPS of M. ovipneumoniae induces a caspase-dependent apoptosis via both intrinsic and extrinsic apoptotic pathways in sheep bronchial epithelial cells, which may be mainly attributed by a ROS-dependent JNK and p38 MAPK signaling pathways.